Deposition path planning-integrated structural topology optimization for 3D additive manufacturing subject to self-support constraint. (October 2017) - Liu, Jikai; To, Albert C.
Abstract: This paper presents a novel level set-based topology optimization implementation, which addresses two main problems of design-for-additive manufacturing (AM): the material anisotropy and the self-support manufacturability constraint. AM material anisotropy is widely recognized and taking it into account while performing structural topology optimization could more realistically evaluate the structural performance. Therefore, both build direction and in-plane raster directions are considered by the topology optimization algorithm, especially for the latter, which is calculated through deposition path planning. The self-support manufacturability constraint is addressed through a novel multi-level set modeling. The related optimization problem formulation and solution process are demonstrated in detail. It is proved by several numerical examples that the manufacturability constraints are always strictly satisfied. Marginally, the recently popular structural skeleton-based deposition paths are also employed to assist the structural topology optimization, and its characteristics are discussed. Highlights: This paper presents a deposition path planning-integrated structural topology optimization method for 3D additive manufacturing. Local material anisotropy is addressed by considering the build direction and the in-plane raster directions. The support-free manufacturability constraint is addressed through a novel multi-level set modeling. Both the contour-offset and structural skeleton-based deposition path patterns have been considered.